2022
DOI: 10.1186/s12864-022-08560-2
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering resistance to Zymoseptoria tritici in the Tunisian durum wheat landrace accession ‘Agili39’

Abstract: Background Septoria tritici blotch (STB), caused by Zymoseptoria tritici (Z. tritici), is an important biotic threat to durum wheat in the entire Mediterranean Basin. Although most durum wheat cultivars are susceptible to Z. tritici, research in STB resistance in durum wheat has been limited. Results In our study, we have identified resistance to a wide array of Z. tritici isolates in the Tunisian durum wheat landrace accession ‘Agili39’. Subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 86 publications
0
11
1
Order By: Relevance
“…In this study, the four identified MSR-QTLs are likely to provide resources for the development of Z. tritici resistant cultivars both in Australia and globally. In comparison to previously published studies, our detected MSR-QTL QStb.wai.1B.1 was co-located with QStb.cim-1BS (Dreisigacker et al, 2015), and the locus of QStb.wai.2B.1 colocated with QTL-2BL, Qstb2B_1 (Aouini, 2018;Ferjaoui et al, 2021) and the major gene Stb9 (Chartrain et al, 2009). While the locus of QStb.wai.5A.1 co-located with QStb.cim-5AL-2 (Dreisigacker et al, 2015) and QStb.B22-5A.a (Naz et al, 2015).…”
Section: Qtls Associated With Multi-stage Resistancecontrasting
confidence: 51%
See 1 more Smart Citation
“…In this study, the four identified MSR-QTLs are likely to provide resources for the development of Z. tritici resistant cultivars both in Australia and globally. In comparison to previously published studies, our detected MSR-QTL QStb.wai.1B.1 was co-located with QStb.cim-1BS (Dreisigacker et al, 2015), and the locus of QStb.wai.2B.1 colocated with QTL-2BL, Qstb2B_1 (Aouini, 2018;Ferjaoui et al, 2021) and the major gene Stb9 (Chartrain et al, 2009). While the locus of QStb.wai.5A.1 co-located with QStb.cim-5AL-2 (Dreisigacker et al, 2015) and QStb.B22-5A.a (Naz et al, 2015).…”
Section: Qtls Associated With Multi-stage Resistancecontrasting
confidence: 51%
“…Further, the QTLs, QTL-2BL and Qstb2B_1 were also mapped from the durum wheat ‘Agili 39’and are reported to be responsible for Z. tritici resistance at both seedling stage and adult-plant stage using multiple isolates. It has also been suggested that this locus could be the major gene Stb9 ( Aouini, 2018 ; Ferjaoui et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As pivotal examples leaf and stem rust resistance sources were mapped in the Portuguese DW landraces PI 192051 and Aus26582, by developing RIL mapping populations, beside alternative contribution from other sources (Qureshi et al, 2017;Qureshi et al, 2018;Aoun et al, 2019). Similarly, a resistance gene to Zymoseptoria tritici was mapped in the Tunisian DW landrace 'Agili 39' (Ferjaoui et al, 2022).…”
Section: Environmental Adaptation Traits From Durum Wheat Landracesmentioning
confidence: 99%
“…tritici , and (b) mapping resistance genes requires the use of specific isolates with pathogenicity to DW as the majority of Z . tritici –BW‐derived isolates are nonpathogenic on DW, known as host species specificity (Ferjaoui et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted in Tunisia with regard to DW landraces have shown that these latter may harbour sources of resistance to Z . tritici (Ben M'Barek et al, 2022; Ferjaoui et al, 2022). Ferjaoui et al (2022) demonstrated that the observed STB resistance in the Tunisian landrace Agili39 is due to two minor and two major quantitative trait loci (QTLs) acting in an additive mode and provided evidence that the broad efficacy of this resistance was due to a natural pyramiding of these QTLs.…”
Section: Introductionmentioning
confidence: 99%